Back Cover: Mapping the Trajectory of Nucleophilic Substitution at Silicon Using a peri‐Substituted Acenaphthyl Scaffold (Chem. Eur. J. 44/2017). Issue 44 (5th July 2017) - Hupf, Emanuel; Olaru, Marian; Raţ, Ciprian I.; Fugel, Malte; Hübschle, Christian B.; Lork, Enno; Grabowsky, Simon; Mebs, Stefan; Beckmann, Jens
Abstract : The nucleophilic substitution reaction of second order (SN 2) at a silicon atom is scrutinized using snapshots along a pseudo‐reaction coordinate, starting with an experimentally isolated phosphino‐fluorosilane as a model for the ion‐molecule complex and the corresponding silylphosphonium cation as a model of the product. It is crucial to combine different bonding descriptors from real and orbital space to understand the pseudo‐reaction; they reveal different aspects based on the different sensitivity to dispersive, electrostatic and polar‐covalent contributions to bonding. More information can be found in the Full Paper by S. Grabowsky, S. Mebs, J. Beckmann et al. onpage 10568 .